0976 The Healthy Sleep Program Quality Improvement Initiative. (12th April 2019) - Weaver, Matthew D; Smith, Brad; O'Brien, Conor S; Viyaran, Natalie; Qadri, Salim; Davidson, Judith R; Stenstrom, Philippe; Denesle, Régine; Barger, Laura K; Quan, Stuart F; Czeisler, Charles A
Abstract: Introduction: Sleep deficiency is associated with detrimental health, mood and performance. Sleep health education, combined with screening and access to treatment for common sleep disorders, may be an effective countermeasure. We conducted a 6-month prospective evaluation of a quality improvement initiative designed to improve sleep health in the workplace. Methods: Employees were emailed a link to sleep health and sleep disorders education. After viewing the education, participants were administered a baseline questionnaire that included validated screening instruments for sleep disorders, anxiety, and depression. Absenteeism and presenteeism were calculated using the World Health Organization Health and Work Performance Questionnaire. Participants who screened positive for a sleep disorder were notified and given the option to share their information with a healthcare provider. Monthly follow-up surveys evaluated the impact of the program on sleep hygiene, mood, and productivity. Results: Invitations were sent to 1, 812 employees; 38% viewed the education and 32% (n=633) completed the baseline questionnaire. The mean age of participants was 41.7 (SD 9.8) years with mean body mass index 26.4 (SD 5.8). Most reported female gender (76%). More than one third (36%) screened positive for a sleep disorder. The prevalence of clinically significant insomnia was 22%, obstructive sleep apnea 19%, and restless legs syndrome 5%. Positive sleep disorder screening was associated with moderate-severe psychological distress (OR 5.46, 95% CI 2.84-10.51) and sleep-related work impairment (OR 5.06, 95% CI 2.94-8.72). Absenteeism and presenteeism costs were $385 per person per month higher (95% CI $251-$519) in the sleep disorder group. Among those who screened positive and participated prospectively, 21% reported seeking a diagnostic evaluation and 9% reported obtaining an evaluation. The subset of participants who screened positive and ultimately received treatment for a sleep disorder (n=19) reported increased sleep quality (p<0.01), reduced fatigue (p=0.05), improved workplace productivity (p=0.02), and increased quality of life (p<0.01). Conclusion: Sleep disorders are common and are associated with reduced workplace performance. Sleep health education with an enhanced bridge to treatment for common sleep disorders can improve self-reported health and productivity. Support (If Any): Conducted in partnership with Haleo Preventive Health Solutions.